2015
DOI: 10.1371/journal.pone.0117538
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Genetics of Threatened Hippocampus guttulatus in Vulnerable Habitats in NW Spain: Temporal and Spatial Stability of Wild Populations with Flexible Polygamous Mating System in Captivity

Abstract: This study was focused on conservation genetics of threatened Hippocampus guttulatus on the Atlantic coast of NW Iberian Peninsula. Information about spatial structure and temporal stability of wild populations was obtained based on microsatellite markers, and used for monitoring a captive breeding program firstly initiated in this zone at the facilities of the Institute of Marine Research (Vigo, Spain). No significant major genetic structure was observed regarding the biogeographical barrier of Cape Finisterr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 91 publications
(137 reference statements)
2
17
0
Order By: Relevance
“…() and L贸pez et al. (), we challenged the initial interpretation of barriers to dispersal against the alternative hypothesis of reproductive isolation between semi鈥恑solated genetic backgrounds coinciding with oceanographic barriers. We describe five cryptic semi鈥恑solated lineages: two lineages in the Atlantic Ocean with a parapatric distribution, two lineages in the Mediterranean Sea with a patchy fine鈥恎rained environment association (lagoon vs marine environments), and one in the Black Sea.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…() and L贸pez et al. (), we challenged the initial interpretation of barriers to dispersal against the alternative hypothesis of reproductive isolation between semi鈥恑solated genetic backgrounds coinciding with oceanographic barriers. We describe five cryptic semi鈥恑solated lineages: two lineages in the Atlantic Ocean with a parapatric distribution, two lineages in the Mediterranean Sea with a patchy fine鈥恎rained environment association (lagoon vs marine environments), and one in the Black Sea.…”
mentioning
confidence: 87%
“…, or across the Cape Finisterre oceanographic barrier, L贸pez et al. ). Four well鈥恉ifferentiated genetic clusters, each distributed over extended regions, were delineated by genetic discontinuities corresponding to usual delimitations between vicariant marine lineages (Woodall et al.…”
mentioning
confidence: 99%
“…Therefore, this higher similarity on bacterial fingerprints among seahorses from the same location is a good indicator that this methodological approach holds the potential to reveal local signatures and allow the tracing of the place of origin of live seahorses. Further genetic information on these wild populations of seahorses, obtained through non-lethal sampling approaches (e.g., sampling dorsal fin or skin filaments as described by L贸pez et al (2015)), will be important to validate this hypothesis in future studies. The present study also showed that bacterial communities present in the skin mucus of seahorses in the wild may vary over short-time periods (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Each individual sample was preserved and stored in 96% ethanol for subsequent genetic analyses. Whole genomic DNA was extracted following either Woodall et al (2015), L贸pez et al (2015) or using a standard CetylTrimethyl Ammonium Bromide (CTAB) Chloroform:Isoamyl alcohol (24:1) protocol (Doyle and Doyle 1987). For samples from Vigo (Spain), the whole genome was amplified using the GenomiPhi kit (GE HealthCare) according to the manufacturer's protocol.…”
Section: Figurementioning
confidence: 99%
“…However, genetic differentiation proved to be very weak over very large geographic distances based on the two genetic studies conducted to date with microsatellite loci (e.g. from the United Kingdom to North of Spain, Woodall et al 2015, or across the Cape Finisterre oceanographic barrier, L贸pez et al 2015). Four welldifferentiated genetic clusters, each distributed over extended regions, were delineated by genetic discontinuities corresponding to usual delimitations between vicariant marine lineages (Woodall et al 2015) -between the Iberian Peninsula and the Bay of Biscay in the North Eastern Atlantic, between the Atlantic Ocean and the Mediterranean Sea, and between the Mediterranean and Black Seas.…”
Section: Introductionmentioning
confidence: 99%